Precise medication for tumor patients in the context of mental stress. (30th October 2021) - Geng, Qi-Shun; Shen, Zhi-Bo; Zheng, Yuan-Yuan; Xue, Wen-Hua; Li, Li-Feng; Zhao, Jie
Cancer is the leading cause of disease-related death worldwide due to its late diagnosis and poor outcomes. Precision medicine plays an important role in the treatment of tumors. As found for many types of tumors, mental stress plays a vital role in the promotion and progression of tumors. In this paper, we briefly introduce the manifestation and effects of mental symptoms in tumor patients. We next specifically discuss the multiple roles of precision medicine in the tumor therapy. Finally, we also highlight the precision medicine strategy for psychiatric symptoms in tumor patients, which promises to enhance the efficacy of tumor therapy.